Criminal Investigation of Cybercrimes - Al-Tumi, Hamza Mohammed; Emhmed, Ali Saad; Al-Zeniqri, Ramadan Mohammad (The annual Scientific Conference for Under and Postgraduate Students at the University., 2024)
Cybercrimes are a new type of crime that has emerged due to modern information and communication technology. These crimes differ significantly from traditional crimes in terms of their components, methods of commission, and the virtual environment in which they occur, as well as the privacy of their perpetrators. This makes them an unfamiliar phenomenon in traditional criminal law texts, both substantively and procedurally. Therefore, attempting to apply traditional investigation and evidence procedures to this new type of crime will not meet the requirements of the principle of procedural legality and will lead to many obstacles for investigative authorities. With the increasing rates of cybercrimes and their impact on various aspects of life due to their connection to the internet, countries have been forced to amend their traditional procedural texts to become effective in combating these crimes, until new texts are established that match the specific nature of cybercrimes and keep pace with the accompanying developments and changes.